Chemical Screening and Antioxidant Activity of Ethyl Acetate Fraction and Residue from Lansium domesticum Ethanolic Extract - Pratiwi Apridamayanti; Rafika Sari (Borneo Journal of Pharmacy, 2023)
Langsat (Lansium domesticum) is a plant that thrives in the tropics. The search for photoprotective compounds derived from natural ingredients has been intensively conducted to develop cosmetic formulations to obtain safe and protective products against UV rays. This study aims to identify chemical compounds in the ethyl acetate fraction and residues of ethanol extract from L. domesticum bark using tube and gas chromatography-mass spectrophotometry tests. At the same time, the antioxidant activity and SPF values were assessed with the DPPH and FRAP methods. The qualitative GC-MS test obtained the percentage peak value and molecular weight. Furthermore, the antioxidant activity was tested using the compound DPPH measured with an ELISA reader at a wavelength of 515.5 nm with UV/vis spectrophotometer and FRAP method using FeCl3 and TPTZ compounds at 615 nm. The SPF value was assessed using Mansur's formula with UV/Vis spectrophotometer at 290 to 320 nm. The results obtained in the ethyl acetate fraction showed terpenoids, while the residue contains phenolics, flavonoids, tannins, and saponins. The GC-MS tests found that the ethyl acetate fraction had 47 types of chemical compounds, including terpenoids and fatty acids group; in the residue, four classes were found, with terpenoid and fatty acid groups being more predominant. Based on the results, the ethyl acetate fraction has an IC50 value of 341.25±26.45 µg/ml and 436.3±10.8 µg/ml; the residue was 94.72±34.22 µg/ml and 2602.79±11.8 µg/ml. Additionally, the SPF values ​​for both were 2.87 and 3.9.